A review of high PV penetrations in LV distribution networks: Present status, impacts and mitigation measures - Haque, M.; Wolfs, Peter (Elsevier Science Ltd, 2016)
© 2016 Elsevier Ltd. All rights reserved. The installed capacity of photovoltaic (PV) systems globally reached 177 GW at the end of 2014. The annual rate of installations, 38.7 GW in 2014, continues to increase. A large part of this is installed as residential systems connected to low voltage (LV) networks. The majority of the LV distribution networks are radial, unbalanced with respect to loads and feeder structures and have high R/X ratios. The large scale deployment of PV within the LV distribution networks is limited by voltage quality problems, particularly over voltages and unbalance. Development of proper mitigation techniques is essential to effectively and efficiently manage high penetration of PV within the LV distribution networks. A number of techniques have already been developed and implemented in LV distribution networks to alleviate those problems. This paper provides an extensive review of the present status, impacts and technical challenges of PV penetration in LV distribution networks. In addition, the review comprehensively examines the commercially available and emerging mitigation methods and provides a framework that systematically explores the full range of technical methods and limitations for PV impact mitigation. These will provide a useful framework and strong point of reference for the researchers working further in this field.